Derivation of a family of high step‐up tapped inductor SEPIC converters. Issue 22 (1st October 2014) - Abramovitz, Alexander; Yao, Jia; Smedley, Keyue
Abstract : A family of single‐switch SEPIC‐derived converters, which apply a tapped inductor (TI), a charge pump (CP) and an inductorless regenerative snubber to attain a high DC step‐up at high efficiency is introduced. The proposed converter family has the advantage of continuous input current, which can be helpful in attaining accurate tracking of the maximum power point of solar panels. The feasibility of the proposed topology is verified by simulation and experimental results.